Acid‐Activated Carbon Materials: Cheaper Alternative Catalysts for the Synthesis of Substituted Quinolines. Issue 12 (17th September 2013) - López‐Sanz, Jesús; Pérez‐Mayoral, Elena; Soriano, Elena; Omenat‐Morán, Delia; Durán, Carlos J.; Martín‐Aranda, Rosa María; Matos, Ines; Fonseca, Isabel
Abstract We describe the first examples of Friedländer reactions efficiently catalyzed by carbon materials. We report herein a series of acidic activated carbon materials, which can be considered as an environmentally friendly, cheaper alternative to the traditional acidic mesoporous silicates or even zeolites for the synthesis of quinolines/quinolones. Textural parameters of the acidic activated carbon materials together with their acidic properties are important factors that affect the reaction selectivity. Some mechanistic details have been addressed by computational calculations.